The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3389/fevo.2018.00074
|View full text |Cite
|
Sign up to set email alerts
|

An Online Experimental Framework for Cooperative Relationships With a Real-Time Decision-Making and Rewarding Environment

Abstract: This paper investigates interactions between game theoretical strategies and social relationships in real-time decision-making and rewarding environments. We propose an experimental framework based on techniques of web-based multiplayer online games for this purpose. In our framework, multiple human players, represented as particles in a two-dimensional space of social interactions, can modify their positions and game strategies for the prisoner's dilemma in real time, and receive benefit or cost emerging from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
(35 reference statements)
1
3
0
Order By: Relevance
“…They observed repeated occurrences of explosive dynamics that consisted of a formation of an altruistic cluster followed by its collapse with explosive dispersal of defective particles. The similar dynamics were observed both computationally and experimen-tally (see (Suzuki et al, 2018)). However, it is still not clear whether and how the significant increase in the scale of social networks, as discussed above, can bring about more diversity and demonstrate emerging patterns for higher-level interactions.…”
Section: Introductionsupporting
confidence: 79%
“…They observed repeated occurrences of explosive dynamics that consisted of a formation of an altruistic cluster followed by its collapse with explosive dispersal of defective particles. The similar dynamics were observed both computationally and experimen-tally (see (Suzuki et al, 2018)). However, it is still not clear whether and how the significant increase in the scale of social networks, as discussed above, can bring about more diversity and demonstrate emerging patterns for higher-level interactions.…”
Section: Introductionsupporting
confidence: 79%
“…The analyses identified weak correlations indicating that a high inclination to alter In order to conduct a comparative analysis between two distinct instances of communication, specifically one that takes place in a physical environment and the other in a virtual environment, we conducted a face-to-face experiment and a web-based experiment with the same five participants while keeping the same payoff matrix. The face-to-face experiment used the current proposed framework, and the web-based experiment used a framework developed by Suzuki et al (2018) based on the SPS model, which consists of human participants interacting with each other online through a computer.…”
Section: Resultsmentioning
confidence: 99%
“…Real-time decision making, well represented in the SPS model, has also received much attention in experimental studies with human participants (Friedman & Oprea, 2012;Hawkins & Goldstone, 2016;Janssen et al, 2014). Suzuki et al (2018) analyzed continuous social dynamics in real human groups by implementing a web-based multiplayer game based on the SPS model, in which human participants, represented as anonymous particles in a shared 2D space, can change their positions and gametheoretical strategies in real time according to the benefits or costs arising from social relationships with neighboring players. They found that the formation and collapse of cooperative clusters emerged in parallel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation